Discounts or gifts? Not just to save money: A study on neural mechanism from the perspective of fuzzy decision. Issue 1 (1st November 2018) - Gong, Yanping; Hou, Wei; Zhang, Qin; Tian, Shuang
Abstract : Purpose: Decision theory holds that the ambiguity of decision information affects the choices of decision makers, who have the emotion of "ambiguity aversion" when making fuzzy decisions. The purpose of this paper is to explore the neural mechanism how the information ambiguity of different sales promotion strategies influences consumers' purchasing decision. Design/methodology/approach: The paper uses the event-related potential (ERP) technique and experiment. Findings: Results indicate that the information ambiguity of sales promotion strategies did influence the purchasing decision of consumers, and there were significant differences in the amplitudes of brain wave P2, N2 and P3 when consumers encountered the sales promotions of different types (discounts and gift-giving). This reflects the difference in perceived risk, decision-making conflict and decision-making attitude. It means that compared with discounts, the perceived risk and difficulty increased while the decision-making confidence plunged when consumers were faced with gift-giving promotions. This finding gives an explanation on the neural level why consumers prefer discounts, rather gift-giving sales promotions. Practical implications: For the merchants to promote commodities online, it is suggested that the actual benefit from the sales promotion should be specified to reduce the ambiguity of sales promotion information. As the neuromarketing develops, merchants have obtained more effective approaches to study marketing strategies. Originality/value: One of the theoretical contributions this paper made is that the authors innovatively explored the consumer's preference to online sales promotion strategies from the perspective of fuzzy decision. Second, the authors adopted the ERP technique to study the influence of the ambiguity of sales promotion information on the consumer's purchasing behaviors. Third, this study provides an explanation for why consumers prefer the sales promotion type of discounts according to the neural mechanism of decision making.